Feasibility Study of Legislation in Religious Thoughts after the Islamic Revolution of Iran - ali maleki (رهیافتهای سیاسی و بین المللی)
Law is one of the modern concepts that has been presented to Muslim scholars since the Qajar government. The possibility of customary legislation has always been a problem of thought and has become a point of contention for religious ideas after the Islamic Revolution. The lack of theoretical arguments and basic agreement in explaining its exact position has caused widespread practical challenges. This research seeks to; descriptive-analytical and comparative method; in the framework of critical theory, answer the question that; from the point of view of religious ideas after the Islamic Revolution of Iran, is customary legislation possible in public affairs or not? After the Islamic Revolution, two types of religious ideas about the possibility or refusal of law have emerged. From the point of view of the supporters of traditional religious thought, legislation is done only by jurists and customary legislation is considered as a kind of polytheism in the Lordship, but from the point of view of religious modernism, customary legislation is possible due to human rights, equality and freedom in political life. The aim of this article is to examine the views of the supporters of religious ideas after the Islamic Revolution in a precise and clear manner and to propose dialogue in a free and independent space and to submit to the democratic game in order to achieve a common discourse on legislation.